2008
DOI: 10.1021/jo8019972
|View full text |Cite
|
Sign up to set email alerts
|

Facile Hydrolysis-Based Chemical Destruction of the Warfare Agents VX, GB, and HD by Alumina-Supported Fluoride Reagents

Abstract: A facile solvent-free hydrolysis (chemical destruction) of the warfare agents VX (O-ethyl S-2-(diisopropylamino)ethyl methylphosphonothioate), GB (O-isopropyl methylphosphonofluoridate or sarin), and HD (2,2'-dichloroethyl sulfide or sulfur mustard) upon reaction with various solid-supported fluoride reagents is described. These solid reagents include different alumina-based powders such as KF/Al(2)O(3), AgF/KF/Al(2)O(3), and KF/Al(2)O(3) enriched by so-called coordinatively unsaturated fluoride ions (termed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 35 publications
3
60
0
Order By: Relevance
“…According to this suggestion, a fluoride ion reacts as a base to deprotonate water to afford a hydroxide ion that can attack the central phosphorus atom. 35 However, we did not exclude the possibility of an alternative mechanism by which the fluoride ion itself attacks the phosphorus atom to form a fluoridate intermediate, which immediately reacts with the basic surface of the alumina and water to furnish the final product EMP. According to both mechanisms, at the last stage of the hydrolysis, fluoride strongly binds to the alumina surface to form a strong Al−F bond.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…According to this suggestion, a fluoride ion reacts as a base to deprotonate water to afford a hydroxide ion that can attack the central phosphorus atom. 35 However, we did not exclude the possibility of an alternative mechanism by which the fluoride ion itself attacks the phosphorus atom to form a fluoridate intermediate, which immediately reacts with the basic surface of the alumina and water to furnish the final product EMP. According to both mechanisms, at the last stage of the hydrolysis, fluoride strongly binds to the alumina surface to form a strong Al−F bond.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 97%
“…34−38 Among other reactions examined, hydrolysis reactions of organophosphorus (OP) warfare agents, which hold relatively good leaving groups, with alumina-supported fluoride reagents were specifically investigated. 35,37 Typically, impregnation of potassium fluoride on the surface of neutral alumina leads to the formation of a heterogeneous support, which is effective in a variety of substitution, elimination, addition, and condensation reactions. 44−52 However, from our studies, we concluded that standard KF/Al 2 O 3 supports do not contain "available" (not connected to the surface) fluoride ions that are required for effective hydrolysis but rather hold hydroxide ions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Examples of the influence of OP hydration include the observation of Henry's law deviations for the vapor pressure of Sarin (GB) over water [1], the acceleration of Sarin hydrolysis in humid environments, the pH and water quality dependence of Sarin hydrolysis [2], the moderate enhancement of Sarin photo-degradation with increasing relative humidity (RH) levels [3], and the reduction of volatility for the CWA simulant dimethyl methylphosphonate (DMMP) with increasing relative humidity (RH) [4]. Water is also known to directly impact the breakthrough, degradation and adsorption energies of OPs on a variety of different surfaces [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[4b] As far as inorganic salts are concerned, solvent-free hydrolysis-based chemical destruction of various warfare agents has been described using alumina-supported fluoride reagents [14] or nanosize inorganic oxide particles. [15] Among the enzyme-mediated bioremediation methods recently reported, most promising are the exogenous administration of acetyl cholinesterase or human butyryl cholinesterase used as a stoichiometric trap.…”
Section: Introductionmentioning
confidence: 99%